A millimeter wave low dielectric constant polyphenylene sulfide material and preparation method thereof

By preparing a modified polymer with a three-stage structure of polyphenylene sulfide-alkyl-polyetherimide, and using supercritical fluid microporous foaming technology, the polyphenylene sulfide material was solved in the microporous foaming process. The problems of crystallinity and brittleness have achieved comprehensive performance improvements of low dielectric constant and high toughness, and are suitable for millimeter wave applications.

CN118126530BActive Publication Date: 2024-12-17SHANGHAI JUZHEN DONGLAI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410355851.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2024-12-17
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

The existing polyphenylene sulfide materials have high crystallinity during microporous foaming, which hinders the impregnation and dissolution of gas, inhibits bubble growth, resulting in brittle and fragile material properties, and unstable foaming agents lead to uneven material properties, which is difficult to meet the low mediation. Electricity constant and high toughness requirements.

Method used

By preparing a modified polymer with a three-stage structure of polyphenylene sulfide-alkyl-polyetherimide, the proportion of copolymer segments is adjusted to reduce crystallinity, and micropore foaming is performed using supercritical fluid method to control pore size To reduce the dielectric constant, improve the toughness of the material, and avoid instability caused by foaming agents.

Benefits of technology

It is achieved to obtain a polyphenylene sulfide material with a microporous structure, the dielectric constant is reduced to the appropriate range, and the material toughness is improved, and the performance inequality caused by foaming agents is avoided, and the low dielectric constant requirements for millimeter wave applications are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004761291860000071
    Figure BDA0004761291860000071
Patent Text Reader

Abstract

A low dielectric constant polyphenylene sulfide material for millimeter waves, comprising the following raw materials in parts by mass: 300-400 parts of modified polyphenylene sulfide, 10-20 parts of lubricant, and 4-7 parts of dispersant, wherein the modified polyphenylene sulfide is a three-stage structure of polyphenylene sulfide-alkyl segment-polyetherimide, the weight average molecular weight of the polyphenylene sulfide segment is 6-100,000, the alkyl group is a straight or branched alkyl group with 10-20 carbon atoms, and the weight average molecular weight of the polyetherimide is 15-20,000. The present invention introduces a C10-20 alkyl segment and polyetherimide by adjusting the modified polyphenylene sulfide, so that the polymer can reduce its crystallinity while maintaining the basic characteristics of polyphenylene sulfide, and can also improve its toughness and molten state fluidity, and then the polyphenylene sulfide composite material is prepared into a microporous structure by supercritical fluid microporous foaming injection molding, which further reduces the dielectric constant of the material and improves the mechanical properties of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a low dielectric constant polyphenylene sulfide material for millimeter waves and a preparation method thereof. Background Art

[0002] Millimeter waves are electromagnetic waves with a wavelength of 1 to 10 mm (frequency of 30 to 300 GHz). They belong to the wavelength range where microwaves and far-infrared waves overlap, and have the characteristics of both spectra. The theory and technology of millimeter waves are the extension of microwaves to high frequencies and the development of light waves to low frequencies. Millimeter waves have a large number of applications in the fields of communications, radar, guidance, remote sensing technology, radio astronomy, clinical medicine, and spectroscopy. Since the 1980s, due to the growing demand for millimeter wave technology, a wave of development of millimeter wave technology has been formed. Millimeter wave technology has made major breakthroughs in the development of transmitters, receivers, antennas, and millimeter wave devices, and various applications have entered a new stage.

[0003] At present, the most revolutionary aspect of 5G technology is the use of high-frequency communication technology, namely 5G millimeter wave technology, which uses the 26-40GHz spectrum and is an important basic technology in 5G applications. However, at such high frequencies, many technologies, equipment and materials face many challenges, because high-frequency signals will cause severe transmission losses, require higher power and more efficient power supplies, and generate more heat. Transmission loss is a pain point for antenna design and RF integrated circuits in 5G applications. As the frequency moves towards millimeter waves, the size of antenna elements will continue to decrease. Therefore, the antenna array can be placed in the package shell. This integration method will also help shorten the RF path, thereby minimizing transmission losses. Package antennas will require low-loss materials as substrates, electromagnetic interference shielding, molded bottom fill materials, etc. Low-loss materials measure material performance through five key factors: dielectric constant, dissipation factor, moisture absorption rate, cost, and manufacturability, among which dielectric constant is the most critical.

[0004] The dielectric constant is a parameter whose size is mainly determined by the properties of the material itself. There are many factors that affect it, such as the polarity, molecular structure, and crystallinity of the material. The higher the frequency of the electromagnetic wave, the shorter the wavelength, the worse the diffraction ability, and the greater the attenuation of the electromagnetic wave during propagation. The larger the value of the dielectric constant, the greater the impact on the electromagnetic signal, which means that the electromagnetic signal will be greatly weakened. Therefore, in order to minimize the propagation loss of high-frequency signals in the 5G era, the development and application of low-dielectric materials is very important. 5G products generally require the dielectric constant of resin composite materials to be between 2.8-3.2 at 100MHz, while 4G products require the dielectric constant to be below 3.7 at 100MHz.

[0005] Polyphenylene sulfide (PPS) is a semi-crystalline engineering plastic with excellent comprehensive performance. It has excellent thermal stability, electrical insulation, chemical stability, flame retardancy and corrosion resistance. It also has good mechanical properties and dimensional stability, high hardness and strength, and is widely used in electronics, machinery manufacturing, automobile manufacturing, instrumentation, chemical corrosion protection, military and aerospace industries. In millimeter wave technology, PPS has many practical applications. It is mainly used as millimeter wave packaging back cover, electromagnetic shielding material, flame retardant material, etc. The current commercial use of this type of PPS has a dielectric constant between 2.9 and 3.2, and PPS with a lower dielectric constant needs to be further developed. In addition, PPS also has shortcomings such as poor toughness, brittleness, and unstable medium viscosity. Therefore, pure PPS is rarely used, and most of the PPS used is its modified varieties. At present, the main modification methods of low dielectric constant PPS materials include chemical modification and physical modification, such as filling, blending and microporous foaming. Among them, microporous foaming utilizes the property that the dielectric constant of air is close to 1. PPS is physically foamed using supercritical CO2, N2, etc., and sufficient air is introduced to prepare low dielectric constant PPS microporous materials. This microporous material has a lower dielectric constant and better impact toughness, fatigue resistance, specific strength, lower density and cost, which has aroused the interest of researchers.

[0006] At present, the commonly used method for microporous foaming is the solid-state intermittent foaming method. This method is to make the gas enter an unsaturated state near the glass transition temperature of the polymer by heating or rapidly reducing the pressure, introducing bubble nucleation and growth. The dielectric constant value of the PPS microporous material prepared by this method can be reduced to below 2. This foaming technology is relatively mature, with simple equipment and easy control of bubbles. It is a common method for laboratory research on foaming mechanisms. However, the higher crystallinity of PPS will hinder the supercritical gas from impregnating and dissolving in the resin and inhibit the growth of bubbles. Therefore, it is necessary to reduce the crystallinity to promote its good foaming. At the same time, this microporous material is brittle and fragile, and is subject to many restrictions in actual use. Summary of the invention

[0007] In view of the problems existing in the polyphenylene sulfide material prepared by the above-mentioned foaming method, this paper provides a low dielectric constant polyphenylene sulfide material for millimeter waves and a preparation method thereof. First, a modified polyphenylene sulfide is prepared. The modified polyphenylene sulfide has a three-stage structure of polyphenylene sulfide-alkyl-polyetherimide. By adjusting the ratio of each segment in the copolymer, the polymer can reduce its crystallinity while maintaining the basic properties of polyphenylene sulfide, improve its toughness and molten state fluidity, and then the polyphenylene sulfide copolymer is foamed by a supercritical fluid method, and the parameters in the foaming process are adjusted to control the size of the foamed pores, reduce the dielectric constant of the material to a suitable range, and improve the toughness of the material. The polyphenylene sulfide material with a microporous structure obtained by the present invention does not require a foaming agent, which avoids the defect that the foaming agent is unstable and the material performance is not uniform and stable enough.

[0008] The invention provides a low dielectric constant polyphenylene sulfide material for millimeter waves, comprising the following raw materials in parts by mass: 300-400 parts of modified polyphenylene sulfide, 10-20 parts of lubricant, and 4-7 parts of dispersant. The modified polyphenylene sulfide is a three-segment structure of polyphenylene sulfide-alkyl segment-polyetherimide, the weight average molecular weight of the polyphenylene sulfide segment is 60,000-100,000, the alkyl group is a straight chain or branched alkyl group with 10-20 carbon atoms, and the weight average molecular weight of the polyetherimide is 15,000-20,000.

[0009] Furthermore, the modified polyphenylene sulfide is obtained by a preparation method comprising the following steps:

[0010] (1) In an inert atmosphere, halogenated sodium benzenethiophenol undergoes self-condensation to obtain a polyphenylene sulfide having a halogen atom as the terminal group;

[0011] (2) a polyphenylene sulfide having a halogen atom at one end and a C10-20 alkyl having carboxyl groups at both ends undergo a condensation reaction in the presence of an acid binding agent to obtain an intermediate product having carboxyl groups at the end;

[0012] (3) The intermediate product and amino-terminated polyetherimide react in the presence of a condensation agent to obtain modified polyphenylene sulfide.

[0013] Furthermore, in step (1), the halogenated sodium benzenethiophenolate is selected from at least one of chloro sodium benzenethiophenolate and bromo sodium benzenethiophenolate; the inert atmosphere is nitrogen and / or argon atmosphere, and the reaction conditions of the self-condensation in step (1) are: 200-250° C. for 4-8 hours, and the reaction solvent is N-methylpyrrolidone. After the reaction, the product is precipitated in water, washed with water for multiple times, filtered, and dried to obtain a polyphenylene sulfide with a halogen atom as the terminal group.

[0014] Furthermore, in step (2), the C10-20 alkyl group with carboxyl groups at both ends is selected from at least one of dodecyl diacid, tridecyl diacid, tetradecyl diacid, pentadecyl diacid and hexadecyl diacid. The amount of C10-20 alkyl group with carboxyl groups at both ends is 3-5wt% of the mass of polyphenylene sulfide with halogen atoms as the terminal groups; the acid binding agent is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, trimethylamine and pyridine, and the amount is 2-3 times the equivalent. The reaction conditions of step (2) are: react at 60-70°C for 10-15h, dimethylformamide; after the reaction is completed, precipitate with water, wash with clean water, filter and dry to obtain an intermediate product;

[0015] Furthermore, in step (3), the amount of amino-terminated polyetherimide is 20-30wt% of the mass of the intermediate product of step (2); the condensing agent is 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and the amount of the condensing agent is 0.2-0.5wt% of the mass of the intermediate product. The reaction conditions of step (3) are: reaction at 140-160° C. for 5-8h; the reaction solvent is dimethylformamide; after the reaction is completed, the product is precipitated with water, washed with clean water, and dried to obtain the product modified polyphenylene sulfide.

[0016] The polyetherimide is obtained by reacting a diamine and a dianhydride, wherein the diamine is selected from one or more of diphenyl ether diamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether, and p-phenylenediamine; and the dianhydride is selected from one or more of 2,2'-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, bisphenol A dianhydride, bisphenol A diether dianhydride, phthalic anhydride, and bisphenol A-co-4-nitrophthalic anhydride.

[0017] Furthermore, the lubricant is one or more of methyl silicone oil, ethyl silicone oil, polyether modified silicone oil, silicate, phosphate ester, and fluoro oil; the dispersant is one or more of vinyl bisstearamide, stearic acid monoglyceride, and tristearic acid glyceride.

[0018] The present invention also provides a method for preparing a low dielectric constant polyphenylene sulfide material for millimeter waves, characterized in that it comprises the following steps:

[0019] (S1) uniformly mixing the modified polyphenylene sulfide, the lubricant and the dispersant, heating to a temperature above the melting point of the polyphenylene sulfide, melting and stirring, dissolving the supercritical fluid into the hot melt adhesive to reach saturation, and maintaining stability at a constant pressure higher than the critical point pressure to obtain a single-phase melt;

[0020] (S2) The single-phase melt in step 1) is injected into a diffusion chamber through a pump nozzle of a microporous foaming injection molding machine. The temperature of the diffusion chamber is 220-260° C. The pressure of the diffusion chamber is lower than the critical pressure. After the unidirectional melt injection is completed, it is slowly restored to normal pressure and cooled to room temperature to form a micro-foamed product, that is, a low dielectric constant polyphenylene sulfide material for millimeter waves.

[0021] Furthermore, in step (S1), heating to above the melting point of polyphenylene sulfide is heating to 280-300°C; the supercritical fluid is CO2 or N2, and the constant pressure higher than the critical point pressure is 1-5MPa higher than the critical pressure of the supercritical fluid.

[0022] Furthermore, in step (S2), the pressure in the diffusion chamber is 0.5-1 MPa lower than the critical point pressure; slowly recovering to normal pressure and cooling to room temperature are completed within 3-5 hours.

[0023] Preferably, the supercritical fluid is CO2, and the constant pressure higher than the critical point pressure in step (S1) is 9-15Mpa, preferably 10-12Mpa; the pressure in the diffusion chamber in step (S2) is 6-7Mpa.

[0024] Due to the sudden pressure drop, the instability of the supercritical fluid is caused, thereby forming bubble nuclei in the product, and these bubble nuclei gradually grow to generate tiny holes. By adjusting the injection rate of the single-phase melt and the pressure in the mold cavity, the bubble pore size of the foaming material is adjusted to a suitable size, thereby adjusting the dielectric constant of the material. After the supercritical fluid is injected, the temperature and pressure are reduced, so that the supercritical fluid dissolved in the melt begins to overflow stably from the inside, forming a polyphenylene sulfide material with a uniform and stable microporous structure, which has comprehensive excellent performance. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The implementation conditions used in the examples can be further adjusted according to the conditions of the specific manufacturer, and the unspecified implementation conditions are usually the conditions in the conventional experiments. The experimental raw materials used are all commercially available products without secondary processing.

[0026] The polyetherimide used in the present invention is obtained by polycondensation of diphenyl ether diamine and bisphenol A dianhydride, is amino-terminated, has a weight average molecular weight of about 17,000, and PDI=1.6.

[0027] Preparation Example 1: Preparation of modified polyphenylene sulfide

[0028] (1) adding 200 g of sodium chlorothiophenolate and 500 g of N-methylpyrrolidone (NMP) to a reaction container, stirring for 20 min, and then heating to 200-250° C. for self-condensation for 6 h under nitrogen protection to obtain polyphenylene sulfide containing a chlorine bond at the end of the molecular chain. The reaction byproduct is sodium chloride, which is precipitated in water. The precipitate is washed with water for multiple times, filtered, and then the polyphenylene sulfide polymer is dried into powder. The molecular weight of the polyphenylene sulfide is measured by gel permeation chromatography to be about 73,000;

[0029] (2) adding 100 g of the polyphenylene sulfide prepared in step (1) and 500 g of polar solvent N-methylpyrrolidone (NMP) into a three-necked flask, heating to 180° C. and stirring for 30 min under a sealed nitrogen atmosphere to completely dissolve the polyphenylene sulfide; then adding 3.7 g of dodecanedioic acid and 2 equivalents of sodium carbonate, heating to 60° C. and reacting for 12 h under a nitrogen atmosphere to condense the halogenated group at the end of the polyphenylene sulfide molecular chain with the carboxyl group at the end of the dodecanedioic acid molecular chain to form an ester; the product is precipitated in water, washed, filtered, and dried to obtain an intermediate product;

[0030] (3) Take 100 g of the intermediate product prepared in step 2), dissolve it again in 500 g of polar solvent dimethylformamide (DMF), heat it to 180° C. and stir it for 30 min under nitrogen flow to make it completely dissolved, add 30 g of amino-terminated polyetherimide and 0.2 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), heat it to 180° C. and stir it for 6 h to promote the dehydration amidation reaction of the amino group of polyetherimide and the carboxyl group of polyphenylene sulfide to form a modified polyphenylene sulfide having a polyphenylene sulfide-alkyl segment-polyetherimide trisegment, and then precipitate the polymer in water, wash it, and dry it into powder for use.

[0031] Preparation Example 2

[0032] The other conditions were the same as those in Preparation Example 1, except that in step (2), 3.7 g of dodecanedioic acid was replaced by 5 g of hexadecanediol.

[0033] Preparation Example 3

[0034] The other conditions are the same as those in Preparation Example 1, except that in step (3), the amount of amino-terminated polyetherimide used is 20 g.

[0035] Preparation Example 4

[0036] The other conditions are the same as those in Preparation Example 1, except that in step (3), the amount of amino-terminated polyetherimide used is 15 g.

[0037] Example 1

[0038] (S1) 300 parts by mass of the modified polyphenylene sulfide prepared in Preparation Example 1, 10 g of a lubricant polyether-modified silicone oil, and 5 g of a dispersant vinyl bisstearamide were mixed and stirred uniformly, added into a barrel of an injection molding machine preheated to 300° C. for melting and plasticization, and then supercritical CO2 was injected into the melting section of the barrel to saturate the melt, and stabilized under 10.5 MPa to obtain a single-phase melt;

[0039] (S2) The single-phase melt is injected into the diffusion chamber through a pump nozzle under the drive of the screw. The temperature of the diffusion chamber is 240°C and the pressure is 6.7 MPa, so that the dissolution rate of supercritical CO2 in the polymer melt is reduced to induce bubble nucleation. The constant high pressure of 6.7 MPa is maintained to inhibit the growth of bubble nuclei. After all the melt is injected, the pressure is slowly released and the temperature is lowered to room temperature. The room temperature and normal pressure are restored within 3 hours to finally form the foamed product.

[0040] Example 2

[0041] The other conditions are the same as those in Example 1, except that the modified polyphenylene sulfide prepared in Preparation Example 1 is replaced by that prepared in Preparation Example 2.

[0042] Example 3

[0043] The other conditions are the same as those in Example 1, except that the modified polyphenylene sulfide prepared in Preparation Example 1 is replaced by that prepared in Preparation Example 3.

[0044] Example 4

[0045] The other conditions are the same as those in Example 1, except that the modified polyphenylene sulfide prepared in Preparation Example 1 is replaced by that prepared in Preparation Example 4.

[0046] Comparative Example 1

[0047] The other conditions are the same as those in Example 1, except that the modified polyphenylene sulfide prepared in Preparation Example 1 is replaced by unmodified polyphenylene sulfide having a weight average molecular weight of 100,000.

[0048] Comparative Example 2

[0049] (S1) 300 parts by mass of the modified polyphenylene sulfide prepared in Preparation Example 1, 10 g of a lubricant polyether-modified silicone oil, and 5 g of a dispersant vinyl bisstearamide are mixed and stirred uniformly, added into the barrel of an injection molding machine preheated to 300° C. for melting and plasticization, and 10 parts by mass of a foaming agent 4,4′-oxybisbenzenesulfonylhydrazide are added. Then, a polyphenylene sulfide composite material is prepared by foaming with the foaming agent instead of supercritical fluid foaming technology.

[0050] The polyphenylene sulfide composite materials obtained in the above examples and comparative examples were subjected to various performance tests, wherein the dielectric constant test was conducted in accordance with the national standard GB / T 14041, the tensile strength test was conducted in accordance with the national standard GB / T1040, the notched impact strength test was conducted in accordance with the national standard GB / T1843, and the thermal conductivity test was conducted in accordance with the national standard GB / T5990-1986. The test results are shown in the following table:

[0051] Table 1 Performance test results of polyphenylene sulfide composite materials

[0052]

[0053] From the results in the above table, it can be seen that the polyphenylene sulfide foam material prepared by using modified polyphenylene sulfide of polyphenylene sulfide-alkyl segment-polyetherimide tri-segment as the main raw material and the supercritical fluid microporous foaming injection molding technology can significantly reduce the dielectric constant of the material, while also appropriately improving the toughness of the material, and has little effect on the thermal conductivity of the material, which can better meet the requirements of low dielectric constant of the material in millimeter wave applications.

Claims

1. A low dielectric constant polyphenylene sulfide material for millimeter waves, characterized in that: The invention comprises the following raw materials in parts by weight: 300-400 parts of modified polyphenylene sulfide, 10-20 parts of lubricant, and 4-7 parts of dispersant, wherein the modified polyphenylene sulfide is a three-segment structure of polyphenylene sulfide-alkyl segment-polyetherimide, the weight average molecular weight of the polyphenylene sulfide segment is 60,000-100,000, the alkyl group is a linear or branched alkyl group with 12-16 carbon atoms, and the weight average molecular weight of the polyetherimide is 15,000-20,000; The method for preparing the low dielectric constant polyphenylene sulfide material for millimeter waves comprises the following steps: (S1) uniformly mixing the modified polyphenylene sulfide, the lubricant and the dispersant, heating to a temperature above the melting point of the polyphenylene sulfide, melting and stirring, dissolving the supercritical fluid into the hot melt adhesive to reach saturation, and maintaining stability at a constant pressure higher than the critical point pressure to obtain a single-phase melt; the constant pressure higher than the critical point pressure is 1-5 MPa higher than the critical pressure of the supercritical fluid; (S2) The single-phase melt in step 1) is injected into a diffusion chamber through a pump nozzle of a microcellular foaming injection molding machine. The temperature of the diffusion chamber is 220-260°C, and the pressure of the diffusion chamber is 0.5-1MPa lower than the critical point pressure. After the unidirectional melt injection is completed, it returns to normal pressure and cools to room temperature in 3-5 hours to form a micro-foamed product, which is a low dielectric constant polyphenylene sulfide material for millimeter waves.

2. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 1, characterized in that: The modified polyphenylene sulfide is obtained by a preparation method comprising the following steps: (1) Under an inert atmosphere, sodium halogenated benzenethiophenol undergoes self-condensation to obtain a polyphenylene sulfide with a halogen atom as the terminal group; (2) A polyphenylene sulfide having a halogen atom at one end and a C12-16 alkyl having carboxyl groups at both ends undergo condensation reaction in the presence of an acid binding agent to obtain an intermediate product having carboxyl groups at the end; (3) The intermediate product and amino-terminated polyetherimide react in the presence of a condensation agent to obtain modified polyphenylene sulfide.

3. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 2, characterized in that: In step (1), the halogenated sodium thiophenolate is selected from at least one of chloro sodium thiophenolate and bromo sodium thiophenolate; the inert atmosphere is nitrogen and / or argon atmosphere, and the reaction conditions of the self-condensation in step (1) are: 200-250° C. for 4-8 hours, and the reaction solvent is N-methylpyrrolidone.

4. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 2, characterized in that: In step (2), the C12-16 alkyl group with carboxyl groups at both ends is selected from at least one of dodecyl diacid, tridecyl diacid, tetradecyl diacid, pentadecyl diacid, and hexadecyl diacid; the amount of the C12-16 alkyl group with carboxyl groups at both ends is 3-5 wt% of the mass of the polyphenylene sulfide with halogen atoms as the terminal groups; the acid binding agent is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, trimethylamine, and pyridine, and the amount used is 2-3 times the equivalent.

5. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 2, characterized in that: The reaction conditions of step (2) are: reacting at 60-70° C. for 10-15 hours; after the reaction is completed, precipitating with water, washing with clean water, filtering, and drying to obtain an intermediate product.

6. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 2, characterized in that: In step (3), the amount of amino-terminated polyetherimide is 20-30wt% of the mass of the intermediate product of step (2); the condensing agent is 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and the amount of the condensing agent is 0.2-0.5wt% of the mass of the intermediate product; the reaction conditions of step (3) are: reaction at 140-160°C for 5-8h; the reaction solvent is dimethylformamide; after the reaction is completed, the product is precipitated with water, washed with clean water, and dried to obtain the product modified polyphenylene sulfide.

7. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 1, characterized in that: Polyetherimide is obtained by the reaction of a diamine and a dianhydride, wherein the diamine is selected from one or more of diphenyl ether diamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether, and p-phenylenediamine; and the dianhydride is selected from 2,2 , - one or more of bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, bisphenol A dianhydride, bisphenol A diether dianhydride, phthalic anhydride, and bisphenol A-co-4-nitrophthalic anhydride.

8. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 1, characterized in that: The lubricant is one or more of methyl silicone oil, ethyl silicone oil, polyether modified silicone oil, silicate, phosphate ester, and fluorine oil; the dispersant is one or more of vinyl bisstearamide, stearic acid monoglyceride, and tristearic acid glyceride.

9. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 1, characterized in that: In step (S1), heating to above the melting point of polyphenylene sulfide is heating to 280-300°C; the supercritical fluid is CO2 or N2.

10. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 9, characterized in that: The supercritical fluid is CO2, the constant pressure higher than the critical point pressure in step (S1) is 9-15Mpa, and the pressure in the diffusion chamber in step (S2) is 6-7Mpa.

11. The low dielectric constant polyphenylene sulfide material for millimeter waves according to claim 10, characterized in that: The constant pressure higher than the critical point pressure in step (S1) is 10-12Mpa.

Citation Information

Patent Citations

  • Modified polyetherimide foaming material, preparation method and application of modified polyetherimide foaming material in PCB (Printed Circuit Board) substrate

    CN115651405A

  • Polyphenylene sulfide material with low friction coefficient and preparation method thereof

    CN116925547A